2022
DOI: 10.3389/fvets.2022.925773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brucellosis Vaccines: A Comprehensive Review

Abstract: Brucellosis is a bacterial zoonosis caused by Brucella spp. which can lead to heavy economic losses and severe human diseases. Thus, controlling brucellosis is very important. Due to humans easily gaining brucellosis from animals, animal brucellosis control programs can help the eradication of human brucellosis. There are two popular vaccines against animal brucellosis. Live attenuated Brucella abortus strain 19 (S19 vaccine) is the first effective and most extensively used vaccine for the prevention of brucel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 166 publications
0
19
0
1
Order By: Relevance
“…Since the beginning of the twentieth century, there have been a number of inquiries and research projects that have been devoted to developing brucellosis vaccines. The production of vaccines against brucellosis has involved the use of inactivated, live-attenuated, and rough-attenuated vaccines [ 47 ]. Brucella vaccines play an important role in the prophylactic control of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the twentieth century, there have been a number of inquiries and research projects that have been devoted to developing brucellosis vaccines. The production of vaccines against brucellosis has involved the use of inactivated, live-attenuated, and rough-attenuated vaccines [ 47 ]. Brucella vaccines play an important role in the prophylactic control of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination and intensive diagnostics are the primary approaches for brucellosis control worldwide ( 49 , 50 ). The lack of human vaccines and the problems with veterinary vaccines, such as abortion in pregnant animals, have made the development of ideal vaccines that are highly immunogenic, safe, and provide long-lasting protection a hot topic ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several subunit vaccine candidates have also been tested against B. melitensis. For example, Omp31 [101], Omp16 [102], rE2o [103], DnaK [104], OMP25-BLS fusion protein [105], Ndk, Dps, InpB and Aspc [106], etc [107] but none of them can clear the pathogen. Similarly, some studies reported nanoparticles containing Brucella vaccine candidates to induce IgM, IgG and mucosal IgA, together with IL-6, IFN-γ, and IL-12 in animal models [108].…”
Section: Discussionmentioning
confidence: 99%